A method for preparing heat-resistant aluminum alloy
A tailored aluminum alloy composition with controlled element ratios and T6 heat treatment addresses the strength and durability limitations of traditional cylinder head materials, achieving superior mechanical properties for high-temperature automotive applications.
Patent Information
- Application Number
- CN202411826329.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Current automotive cylinder head materials, primarily made from A356 aluminum alloy, have limitations in strength and durability, failing to meet the demands for higher performance and lightweight requirements.
A novel aluminum alloy composition comprising specific weight percentages of Cu, Si, Zn, Mn, Mg, Fe, Sr, Mo, W, and V, along with controlled ratios between these elements, combined with a T6 heat treatment process, to enhance strength and durability.
The alloy achieves enhanced mechanical properties, including high tensile strength, yield strength, and ductility, suitable for high-temperature automotive components, overcoming the limitations of traditional alloys.
Smart Images

Figure CN119265458B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to a method for preparing a heat-resistant aluminum alloy. Background Art
[0002] Ultra-high-strength heat-resistant materials are widely demanded in the field of automobile cylinder heads. From the perspective of technological development trends, the demand for lightweight, high-strength and tough materials will further increase. For example, higher-standard aluminum alloy materials can increase tensile strength and yield strength by more than 30% compared to traditional automobile cylinder head materials. Therefore, for products made of traditional automobile materials, higher-performance heat-resistant aluminum alloy materials can be used as substitutes to reduce the weight of parts and achieve the goal of lightweighting.
[0003] At present, automobile cylinder heads are mostly made of traditional cast aluminum alloy A356, whose maximum yield strength is generally around 200-250MPa and tensile strength is 300-330MPa. This limits the improvement of automobile cylinder head performance to a certain extent and cannot meet the technical requirements of new high-strength materials. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a heat-resistant aluminum alloy to solve the problems raised in the above background technology.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a heat-resistant aluminum alloy material, composed of the following materials: Cu 2.5wt%-4.5wt%, Si 7.5wt%-9.5wt%, Zn 0.5wt%-1.0wt%, Mn≤0.2wt%, Mg 0.3wt%-0.5wt%, Fe≤0.25wt%, Sr 0.01wt%-0.045wt%, Mo 0.05wt%-0.25wt%, W 0.05wt%-0.25wt%, V 0.03wt%-0.15wt%, the balance is Al and impurities, wherein the total impurity content is not more than 0.25wt%.
[0006] As a further improvement of the present invention, the mass fraction relationship between Zn, Mg and Cu is:
[0007] 3.0≤2.0Zn+1.5Mg+0.5Cu≤5.0;
[0008] The mass fraction relationship between Mo, W and Si is:
[0009] 0.025<10(Mo-W) / Si<0.1;
[0010] The mass fraction ratio of Fe / V elements is 2.5-5.
[0011] The invention also discloses a method for preparing the heat-resistant aluminum alloy material, which comprises the following steps:
[0012] S1. Prepare raw materials according to the formula of aluminum alloy materials, weigh corresponding percentages of each raw material, dry and preheat, heat melt and stir evenly to obtain alloy melt;
[0013] S2, refining the alloy melt obtained in step S1 to complete degassing and impurity removal;
[0014] S3, feeding the alloy melt treated in step S2 into a forming device for preparation and forming to obtain an aluminum alloy component, wherein the forming device is a gravity, low pressure or extrusion device;
[0015] S4. Place the cast sample into a heat treatment device for T6 heat treatment.
[0016] As a further improvement of the present invention, the hot melting in S1 includes the following steps: adding the electrolytic aluminum A00 ingot into the smelting furnace for melting, and after it is completely melted, adding pure metal or intermediate alloy of Cu element, Mg element and Zn element, and after it is completely melted, adding Al-Mo, Al-Sr, AlV and AlW intermediate alloy.
[0017] As a further improvement of the present invention, the drying preheating temperature in S1 is 100-450° C., the hot melting temperature is 730-800° C., and the stirring time is 5-15 minutes.
[0018] As a further improvement of the present invention, the refining treatment in S2 includes the following steps: introducing a protective gas into the alloy melt, adding RJ-01 refining agent, the refining time is 15-30 minutes, and the amount of solid refining agent added is 0.2%-0.5% of the melt mass.
[0019] As a further improvement of the present invention, the protective gas is nitrogen or argon, and the amount of the protective gas introduced is 0.15-6 L / min.
[0020] As a further improvement of the present invention, the T6 heat treatment process in the S4 is as follows: the solution temperature is 490-520°C, the holding time is 3-6 hours, the temperature rise is controlled at 5-8°C per minute, the quenching temperature is 50-70 degrees, the transfer time is less than 60 seconds, the artificial aging temperature is 160-185°C, the holding time is 3-6 hours, and the furnace is cooled to room temperature.
[0021] As a further improvement of the present invention, after the heat-resistant aluminum alloy material undergoes T6 heat treatment, the tensile strength of the aluminum alloy component is greater than 450MPa, the yield strength is greater than 380MPa, the elongation after fracture is greater than 2.0%, and the hardness is ≥135HBW;
[0022] After T6 heat treatment, the aluminum alloy components are made into tensile specimens of standard size, heated to 250℃, and kept warm for 30 minutes for high-temperature tensile test. The tensile strength is greater than 280MPa, the yield strength is ≥220MPa, the elongation after fracture is ≥4.0%, and the hardness is ≥85HB.
[0023] The invention also discloses the application of the heat-resistant aluminum alloy material. The heat-resistant aluminum alloy material is applied to the parts of a flywheel housing, a gear chamber, and a cylinder head which are in a high-temperature working environment.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The aluminum alloy composition of the present invention does not contain precious metals such as Ni and Zr, and the elements that may cause poisoning are avoided as much as possible. The design range of the sum of the mass fractions of the elements such as 2.0Zn+1.5Mg+0.5Cu, 10(Mo-W) / Si, Fe / V is designed to achieve multiple effects of fine grain strengthening, dispersion strengthening, and interface coherent strengthening, and fundamentally solve the above problems. The eutectic silicon is refined by strontium modification, and the solid solution strengthening brought by Cu, Mg, and Zn elements is combined. The dispersion strengthening brought by the precipitation of nano-sized Mo-rich and V-rich particles of Mo and V elements during the rapid cooling process is utilized;
[0026] Secondly, trace W elements are added to obtain W by setting appropriate components to react with Si. x Si y (W5Si3 or WSi2) intermetallic compound, the metal compound has a complex crystal structure, usually presents a tetragonal or hexagonal system, I4 / mcm space group, a melting point of up to 2220°C, and has relatively high hardness, wear resistance, corrosion resistance, oxidation resistance and other excellent properties, which makes it have excellent stability in high temperature environment. W alloy has an extremely high melting point and is difficult to melt, and its high density makes it easy to sink to the bottom; therefore, the present invention prepares Al-W intermediate alloy by mechanical crushing, and at the same time, electromagnetically stirs the aluminum liquid; the added W element is mixed evenly with the matrix to avoid agglomeration. W and Mo belong to the same main group element, and the atomic radius and atomic valence of the two are similar, and they have extremely high solid solubility in each other's lattice, so it is necessary to design a reasonable 10(Mo-W) / Si mass fraction ratio range, first generate W x Si y Intermetallic compounds achieve material strengthening effects; at the same time, they do not affect the dispersion and precipitation of Mo elements in the matrix, inhibit the movement and growth of low-melting-point Si phases during high-temperature processes, and give aluminum alloy materials excellent high-temperature mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the organization diagram after heat treatment of the present invention;
[0028] Figure 2 This is a fracture diagram after stretching of the present invention;
[0029] Figure 3 It is the microstructure evolution diagram of the material of the present invention;
[0030] Figure 4 This is a surface scan result of the microstructure of the material of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Lightweighting is an important direction for the development of industrial parts, so aluminum alloy materials are widely used in the manufacturing process of automotive parts. Automobile cylinder heads are an important application scenario for high-temperature resistant aluminum alloys. The high-temperature strength of the material determines the ability of the vehicle's power to maintain continuous stability to a certain extent, which directly affects the safety performance of the vehicle. However, the use environment of the automobile cylinder head places extremely stringent requirements on the material, which creates a certain contradiction with the use of lightweight aluminum alloy materials. In other words, the performance of aluminum alloy materials restricts the development of cylinder heads to a certain extent.
[0033] The improvement of the performance of aluminum alloy materials is mainly focused on the improvement of composition design and smelting preparation methods, which has been introduced in the background technology. In the preparation process of aluminum alloys, the positive and negative effects of various elements on the performance of the finished product have been basically mastered by those skilled in the art. For example, elements such as Zr can form intermetallic compounds during the smelting process, which is conducive to grain refinement, but at the same time it may also cause Si poisoning; Cu can improve the fluidity of the material, but at the same time it will damage the elongation of the material and reduce corrosion resistance; Mg can also improve the strength of the material, but the material's tendency to thermal cracking will also increase. Therefore, the current mainstream improvement of aluminum alloy performance focuses on selecting reasonable elements and the ratio design of each element according to the conditions of use.
[0034] Example 1
[0035] The invention provides a heat-resistant aluminum alloy material, which is composed of the following materials: Cu 2.7wt%, Si 9.0wt%, Zn0.8wt%, Mn 0.05wt%, Mg 0.45wt%, Fe 0.15wt%, Sr 0.025wt%, Mo 0.085wt%, W 0.055wt%, V0.045wt%, and the remainder is Al and impurities, wherein the total impurity content is not more than 0.25wt%, (2.0Zn+1.5Mg+0.5Cu) is 3.625, 10(Mo-W) / Si is 0.033, and the mass fraction ratio of Fe / V elements is 3.33. The heat-resistant aluminum alloy material is applied to parts of a flywheel housing, a gear chamber, and a cylinder head in a high-temperature working environment.
[0036] The preparation method of the high-heat-resistant aluminum alloy material comprises the following steps:
[0037] S1. Prepare raw materials according to the formula of aluminum alloy materials, weigh corresponding percentages of each raw material, dry preheat, heat melt and stir evenly to obtain alloy melt, wherein the drying preheating temperature is 100-450°C, the hot melting temperature is 730-800°C, and the stirring time is 5-15min. Hot melting is to add electrolytic aluminum A00 ingot into a smelting furnace for melting, and then add pure metal or intermediate alloy of Cu element, Mg element and Zn element after it is completely melted, and then add Al-Mo, Al-Sr, AlV and AlW intermediate alloy after it is completely melted. The specific method of adding W element is mechanical crushing method, and the mixture is evenly mixed by electromagnetic stirring to obtain a uniformly distributed melt;
[0038] S2, refining the alloy melt obtained in step S1 to complete degassing and impurity removal, wherein the refining is to introduce a protective gas into the alloy melt, add RJ-01 refining agent, the refining time is 15-30 minutes, the amount of solid refining agent added is 0.2%-0.5% of the melt mass, the protective gas is nitrogen or argon, and the amount of the protective gas introduced is 0.15-6L / min;
[0039] S3, feeding the alloy melt treated in step S2 into a forming device for preparation and forming to obtain an aluminum alloy component, wherein the forming device is a gravity, low pressure or extrusion device;
[0040] S4. Place the cast sample into a heat treatment device for T6 heat treatment.
[0041] Then carry out T6 heat treatment process, the solid solution temperature of T6 heat treatment process is 490-520℃, the holding time is 3-6 hours, the temperature rise is controlled at 5-8℃ per minute, the quenching temperature is 50-70 degrees, the transfer time is less than 60 seconds, the artificial aging temperature is 160-185℃, the holding time is 3-6 hours, and the furnace is cooled to room temperature.
[0042] After the above-mentioned melting and low-pressure casting, standard specimens are prepared for testing. The main room temperature mechanical properties are as follows: tensile strength 455MPa, yield strength 390MPa, elongation after fracture 3.8%, hardness 140HB, (250℃) high temperature mechanical properties are as follows: tensile strength 290MPa, yield strength 235MPa, elongation after fracture 5.5%, hardness 97HB.
[0043] Example 2
[0044] The present invention provides the following technical solution: a heat-resistant aluminum alloy material, composed of the following materials: Cu 3.2wt%, Si7.8%, Zn 0.55wt%, Mn 0.12wt%, Mg 0.45wt%, Fe 0.16wt%, Sr 0.028wt%, Mo 0.088%, W0.065%, V0.035wt%, the remainder is Al and impurities, wherein the total impurity content is not more than 0.25wt%, (2.0Zn+1.5Mg+0.5Cu) is 0.029, 10(Mo-W) / Si is the element mass fraction ratio of 0.029, and the Fe / V element mass fraction ratio is 4.57.
[0045] The preparation process of Example 1 was adopted.
[0046] The main room temperature mechanical properties of the prepared standard specimens are as follows: tensile strength 474MPa, yield strength 391MPa, elongation at break 3.2%, and hardness 145HB; (250℃) high temperature mechanical properties are as follows: tensile strength 288MPa, yield strength 245MPa, elongation at break 4.8%, and hardness 95HB.
[0047] Example 3
[0048] The present invention provides the following technical solution: a heat-resistant aluminum alloy material, composed of the following materials: Cu 3.5wt%, Si 8.8wt%, Zn 0.65%, Mn 0.10wt%, Mg 0.48wt%, Fe 0.19wt%, Sr 0.023wt%, Mo 0.128%, W 0.085wt%, V 0.052wt%, the remainder being Al and impurities, wherein the total impurity content is not more than 0.25wt%, (2.0Zn+1.5Mg+0.5Cu) is 3.77, the ratio of 10(Mo-W) / Si element mass fraction is 0.049, and the ratio of Fe / V element mass fraction is 3.65.
[0049] The preparation process of Example 1 was adopted.
[0050] The main room temperature mechanical properties of the prepared standard specimens tested are as follows: tensile strength 476MPa, yield strength 397MPa, elongation at break 2.6%, and hardness 147HB; (250℃) high temperature mechanical properties are as follows: tensile strength 285MPa, yield strength 235MPa, elongation at break 5.2%, and hardness 94HB.
[0051] Comparative Example 1
[0052] The raw materials are prepared in the following proportions: Cu 3.2wt%, Si 8.7wt%, Zn 0.5wt%, Mn 0.10wt%; Mg0.48wt%, Fe 0.12wt%, Sr 0.023wt%, and the remainder is Al and impurities, wherein the total impurity content is not more than 0.25wt%, and (2.0Zn+1.5Mg+0.5Cu) is 3.32.
[0053] The preparation process of Example 1 was adopted.
[0054] The main room temperature mechanical properties of the prepared standard specimens are as follows: tensile strength 380MPa, yield strength 337MPa, elongation after fracture 3.6%, hardness 120HB. (250℃) High temperature mechanical properties are as follows: tensile strength 208MPa, yield strength 195MPa, elongation after fracture 6.2%, hardness 75HB. The comparison case does not add high temperature resistant elements such as Mo, W, and V, and the high temperature strength at 250℃ cannot meet the tensile strength greater than 280MPa. It can be seen from the above that under the same conditions, the aluminum alloy material of this application has better high temperature mechanical properties after casting.
[0055] The metallographic structures of the samples prepared in Examples 1, 2, and 3 were observed under an electron microscope and were generally distributed in the same manner (representative structures were selected, see Figure 4 ), as can be seen from the figure, after T6 heat treatment, the elements detected at the black origin after surface scanning are Si and W elements. Combined with the energy spectrum point scanning, the black particles are W x Si y Phase. The formation of high melting point and high hardness phase; improves the temperature resistance of low melting point silicon phase under high temperature conditions, prevents the movement of silicon phase, and makes the distribution of intermetallic compounds more dispersed, the size of the dispersed matter is effectively limited, the segmentation effect on the grain boundary is weakened, and the pinning effect is significantly enhanced; in addition, the 2.0Zn+1.5Mg+0.5Cu ratio and the Fe / V element mass fraction ratio are considered when designing elements, which significantly improves the grain size, the size of the precipitates, and the concentration gradient, giving full play to the combined effect of fine grain strengthening on strength and toughness.
[0056] In order to verify whether the performance of the aluminum alloy prepared by the above preparation method meets the requirements, different batches of finished high-strength aluminum alloys were randomly selected, and their composition and mechanical properties (standard samples) were measured. The results shown in Table 1 were obtained:
[0057] Table 1
[0058] As can be seen from Table 1, the aluminum alloy materials prepared according to the design principle and method of the present application have a tensile strength greater than 450 MPa, a yield strength greater than 380 MPa, an elongation greater than 2.0%, and a hardness greater than 135 HB, which fully meets the requirements of the automotive cylinder head, gear room, and flywheel housing for light weight, high strength, and high temperature resistance. They can be used in the manufacture of automotive cylinder heads and other products, providing excellent materials for reducing the weight of parts and improving power performance.
[0059] The present invention introduces AlSr master alloy and reasonably designs the mass fraction ratio range of 2Zn+1.5Mg+0.5Cu, 10(Mo-W) / Si and Fe / V. Firstly, different diffusion rates of Mo are used to form precipitates of different crystal forms, and a gradient and regularly distributed intermetallic compound is obtained, which is inherited to the aging stage. Secondly, a trace amount of W element is added, and W is obtained by setting appropriate components to react with Si. x Si y Intermetallic compounds, which have a complex crystal structure, usually present as a tetragonal or hexagonal system, I4 / mcm space group, a melting point of up to 2220°C, and have relatively high hardness, wear resistance, corrosion resistance, oxidation resistance and other excellent properties, which makes it have excellent stability in high temperature environments. W alloy has an extremely high melting point and is difficult to melt, and its high density makes it easy to sink to the bottom; therefore, the present invention prepares Al-W intermediate alloys by mechanical crushing, and at the same time, electromagnetically stirs the aluminum liquid; the added W element is mixed evenly with the matrix to avoid agglomeration. W and Mo belong to the same main group elements, and the two have similar atomic radii and atomic valences, and have extremely high solid solubility in each other's lattices. Therefore, it is necessary to design a reasonable 10(Mo-W) / Si mass fraction ratio range, and first generate W x Si y The intermetallic compound achieves the material strengthening effect; at the same time, it does not affect the dispersion and precipitation of the Mo element in the matrix. Adding trace element V to the aluminum alloy can improve the tensile strength and elongation of the aluminum alloy. The V element will precipitate spherical AlFeSi (Mn + V) phase in the matrix, effectively reducing the lamellar iron-rich phase in the matrix, which is beneficial to the improvement of the toughness of the aluminum alloy. Therefore, the mass content of V is controlled to be 0.03-0.15wt%, and the material structure evolution is shown in Figure 3The tensile strength of the aluminum alloy material prepared by the above-mentioned component design and process can be increased to more than 450MPa, and the yield strength can be increased to more than 380MPa. At the same time, the elongation after fracture can still be maintained at 2.0%, and the hardness is ≥135BW. The yield strength and hardness are greatly improved, which is very suitable for automotive parts such as gear chambers, flywheel discs, and cylinder heads.
[0060] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A heat-resistant aluminum alloy material, characterized in that: Composed of the following materials: Cu 2.5wt%-4.5wt%, Si7.5wt%-9.5wt%, Zn 0.5wt%-1.0wt%, Mn≤0.2wt%, Mg 0.3wt%-0.5wt%, Fe≤0.25wt%, Sr0.01wt%-0.045wt%, Mo 0.05wt%-0.25wt%, W 0.05wt%-0.25wt%, V 0.03wt%-0.15wt%, the balance is Al and impurities, wherein the total impurity content is not more than 0.25wt%; The mass fraction relationship between Zn, Mg and Cu is: 3.0≤2.0Zn+1.5Mg+0.5Cu≤5.0; The mass fraction relationship between Mo, W and Si is: 0.025<10(Mo-W) / Si<0.1; The mass fraction ratio of Fe / V element is 2.5-5; After the aluminum alloy components obtained by the forming process of the heat-resistant aluminum alloy material are subjected to T6 heat treatment, the tensile strength of the aluminum alloy components is greater than 450MPa, the yield strength is greater than 380MPa, the elongation after fracture is greater than 2.0%, and the hardness is ≥135HBW; After T6 heat treatment, the aluminum alloy components are made into tensile specimens of standard size, heated to 250℃, and kept warm for 30 minutes for high-temperature tensile test. The tensile strength is greater than 280MPa, the yield strength is ≥220MPa, the elongation after fracture is ≥4.0%, and the hardness is ≥85HB.
2. The method for preparing a heat-resistant aluminum alloy material according to claim 1, characterized in that: The following steps are involved: S1. Prepare raw materials according to the formula of aluminum alloy materials, weigh corresponding percentages of each raw material, dry and preheat, heat melt and stir evenly to obtain alloy melt; S2, refining the alloy melt obtained in step S1 to complete degassing and impurity removal; S3, feeding the alloy melt treated in step S2 into a forming device for preparation and forming to obtain an aluminum alloy component, wherein the forming device is a gravity, low pressure or extrusion device; S4. Place the cast sample into a heat treatment device for T6 heat treatment.
3. The method for preparing a heat-resistant aluminum alloy material according to claim 2, characterized in that: The hot melting in S1 includes the following steps: adding the electrolytic aluminum A00 ingot into a smelting furnace for melting, and after it is completely melted, adding pure metals or intermediate alloys of Cu, Mg and Zn elements, and after it is completely melted, adding Al-Mo, Al-Sr, AlV and AlW intermediate alloys.
4. The method for preparing a heat-resistant aluminum alloy material according to claim 2, characterized in that: In the S1, the drying preheating temperature is 100-450°C, the heat melting temperature is 730-800°C, and the stirring time is 5-15 minutes.
5. The method for preparing a heat-resistant aluminum alloy material according to claim 2, characterized in that: The refining treatment in S2 comprises the following steps: introducing a protective gas into the alloy melt, adding RJ-01 refining agent, the refining time is 15-30 minutes, and the amount of RJ-01 refining agent added is 0.2%-0.5% of the melt mass.
6. The method for preparing a heat-resistant aluminum alloy material according to claim 5, characterized in that: The protective gas is nitrogen or argon, and the amount of the protective gas introduced is 0.15-6 L / min.
7. The method for preparing a heat-resistant aluminum alloy material according to claim 2, characterized in that: The T6 heat treatment process in the S4 is as follows: the temperature is controlled to rise by 5-8°C per minute, the solution temperature is 490-520°C, the holding time is 3-6 hours, the quenching temperature is 50-70 degrees, the transfer time is less than 60 seconds, the artificial aging temperature is 160-185°C, the holding time is 3-6 hours, and the furnace is cooled to room temperature.
Citation Information
Patent Citations
High-strength wear-resistant aluminium alloy material and preparation method thereof
CN109112372A
Explosion-proof and explosion-proof aluminum alloy material and preparation method thereof
CN117646138A
Novel high-temperature-resistant engine cylinder cover aluminum alloy and preparation method thereof
CN117778827A